Characteristics of fatigue in Parkinson’s disease: A longitudinal cohort study - Zhou, Xiaoxia; Xiang, Yaqin; Song, Tingwei; Zhao, Yuwen; Pan, Hongxu; Xu, Qian; Chen, Yase; Sun, Qiying; Wu, Xinyin; Yan, Xinxiang; Guo, Jifeng; Tang, Beisha; et al. (Frontiers in Aging Neuroscience, 2023)
Objective: To assess the prevalence, evolution, clinical characteristics, correlates and predictors of fatigue as well as to investigate the influence of comorbid fatigue on the longitudinal changes in motor and non-motor symptoms over a 2-year longitudinal follow-up period in a large cohort of patients with Parkinson’s disease (PD). Materials and Methods: A total of 2,100 PD patients were enrolled from the Parkinson’s Disease & Movement Disorders Multicenter Database and Collaborative Network in China (PD-MDCNC), and their motor and non-motor symptoms were assessed biennially using comprehensive scales, including the 16-item Parkinson Fatigue Scale (PFS-16). Each PD patient was categorized as PD with or without fatigue on the basis of a cut-off mean PFS-16 score of 3.3. Results: The prevalence of fatigue in our cohort was 36.8%. Compared to PD patients without fatigue, PD patients with fatigue were more likely to be older, have a longer disease duration, and higher baseline levodopa equivalent daily dose (all P < 0.05). Moreover, PD patients with fatigue showed more severe motor and non-motor phenotypes than those without fatigue. Overall, high total Unified Parkinson’s Disease Rating Scale (UPDRS) score (odds ratio [OR]=1.016, 95% confidence interval [CI]: 1.009-1.024), Non-Motor Symptoms Scale score (OR=1.022, 95% CI: 1.015-1.029), postural instability and gait difficulty (PIGD) subtype (OR=1.586, 95% CI: 1.211-2.079), presence of excessive daytime sleepiness (EDS) (OR=1.343, 95% CI: 1.083-1.666), and wearing-off (OR=1.282, 95% CI: 1.023-1.607) were significantly associated with fatigue in PD patients (all P < 0.05). High total UPDRS score at baseline (OR=1.014, 95% CI: 1.002-1.027, P = 0.028) increased the risk of developing fatigue during follow-up. Although significant, the odds ratios were low and confidence intervals were narrow. Analysis of disease progression showed significant group differences in motor and non-motor symptoms. In comparison with the never-fatigue group, the persistent-fatigue group showed significantly greater progression in motor, autonomic dysfunction, sleep, depression and cognitive symptoms (all P < 0.05). Conclusion: Increased disease severity, presence of the PIGD subtype, EDS, and wearing-off were associated with fatigue in PD patients. Significant subgroup-level differences were observed in the progression of motor and non-motor symptoms across different fatigue subgroups of PD patients.